2005
DOI: 10.1093/gerona/60.7.872
|View full text |Cite
|
Sign up to set email alerts
|

Abdominal Adiposity Assessed by Dual Energy X-Ray Absorptiometry Provides a Sex-Independent Predictor of Insulin Sensitivity in Older Adults

Abstract: WHR is not associated with S(I) in either men or women. Abdominal adiposity measured by DXA L1-L4 fat mass provides a sex-independent predictor of S(I) in older men and women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
35
2
5

Year Published

2007
2007
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(44 citation statements)
references
References 58 publications
2
35
2
5
Order By: Relevance
“…Android fat region is an estimate of central fat, while gynoid fat region correlates with peripheral fat. Android fat region has been shown to contain a relative high proportion of intra-abdominal fat and has been validated as a good indirect method of visceral fat prediction (17)(18)(19)(20)(21)(22).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Android fat region is an estimate of central fat, while gynoid fat region correlates with peripheral fat. Android fat region has been shown to contain a relative high proportion of intra-abdominal fat and has been validated as a good indirect method of visceral fat prediction (17)(18)(19)(20)(21)(22).…”
Section: Methodsmentioning
confidence: 99%
“…Regional fat distribution measured by DEXA as gynoid fat and android fat positively correlates with central and peripheral fat measured by MRI, respectively. This technique has been validated as a precise indirect method of visceral abdominal fat determination, with the advantage of having a cost lower than that of CT and MRI and no need of contrast media (17)(18)(19)(20)(21)(22).…”
mentioning
confidence: 99%
“…Studies that have considered the association of the DXA ROI and cardiovascular disease (CVD) and diabetes risk factors have found varying results [12][13][14][15][16]. A study among men and women found the DXA ROI (measured L1-L4) was more predictive of insulin sensitivity than waist index, BMI as well as other DEXA measures (including percent body fat) after controlling for sex [16].…”
Section: Introductionmentioning
confidence: 99%
“…A study among men and women found the DXA ROI (measured L1-L4) was more predictive of insulin sensitivity than waist index, BMI as well as other DEXA measures (including percent body fat) after controlling for sex [16].…”
Section: Introductionmentioning
confidence: 99%
“…Atualmente, sabe-se que o tecido adiposo não representa apenas o maior reservatório de energia no organismo, mas também um órgão com múlti-plas funções e, dependendo dos locais nos quais há deposição de gordura, diferentes respostas biológicas são observadas 2 . Embora as relações de causa e efeito não tenham sido totalmente estabelecidas, as evidências disponíveis indicam que a gordura visceral possui um efeito deletério sobre distintos parâ-metros metabólicos e hemodinâmicos, representando um elo importante entre as diversas facetas da síndrome metabólica 3 , como a resistência à insulina 4 , a intolerância à glicose 5,6 , a hipertensão arterial e as dislipidemias 7 .…”
Section: N T R O D U ç ã Ounclassified